Differential effect of Fas activation on spinal muscular atrophy motoneuron death and induction of axonal growth: Dual signaling of Fas in motoneurons - Benlefki, Salim; Younes, Richard; Challuau, Désiré; Bernard-Marissal, Nathalie; Hilaire, Cécile; Scamps, Frédérique; Bowerman, Melissa; Kothary, Rashmi; Schneider, Bernard L.; Raoul, Cedric (Cellular and Molecular Biology, 2023)
Amyotrophic lateral sclerosis (ALS) and spinal muscular atrophy (SMA) are the most common motoneuron diseases affecting adults and infants, respectively. ALS and SMA are both characterized by the selective degeneration of motoneurons. Although different in their genetic etiology, growing evidence indicates that they share molecular and cellular pathogenic signatures that constitute potential common therapeutic targets. We previously described a motoneuron-specific death pathway elicited by the Fas death receptor, whereby vulnerable ALS motoneurons show an exacerbated sensitivity to Fas activation. However, the mechanisms that drive the loss of SMA motoneurons remains poorly understood. Here, we describe an in vitro model of SMA-associated degeneration using primary motoneurons derived from Smn2B/- SMA mice and show that Fas activation selectively triggers death of the proximal motoneurons. Fas-induced death of SMA motoneurons has the molecular signature of the motoneuron-selective Fas death pathway that requires activation of p38 kinase, caspase-8, -9 and -3 as well as upregulation of collapsin response mediator protein 4 (CRMP4). In addition, Rho-associated Kinase (ROCK) is required for Fas recruitment. Remarkably, we found that exogenous activation of Fas also promotes axonal elongation in both wildtype and SMA motoneurons. Axon outgrowth of motoneurons promoted by Fas requires the activity of ERK, ROCK and caspases. This work defines a dual role of Fas signaling in motoneurons that can elicit distinct responses from cell death to axonal growth.